Analisis Pengelolaan Instagram dalam Penyebaran Informasi Menggunakan Teori The Circular Model SOME - Qadri, Muhammad Aulia Al (Lembaga Yasin AlSys, 2023)
The influence of the speed of information that is easy to obtain is so great that we must be able to choose and sort out what is good and important for our survival, especially the next generation of young people. The management of social media is currently very influential in terms of enhancing corporate and agency image, so it is important to know what social media management is like. The theory in this study is The Circular Model of SOME. This research uses descriptive qualitative method. The results of this study found that Instagram UTS management was not optimal, because; The share has been fulfilled, by selecting the Instagram platform to communicate with the target of communication; Optimize could not be fulfilled, seen from the perception of followers who said that accessing information on the UTS Instagram did not get a clear answer, there was no important thing being done by the UTS Instagram in the form of taking a part in communication in line with the documentation data; Documentation data has proven that 3 important things in the Manage stage have been carried out; Engage has been fulfilled by Instagram UTS in managing its social media and this is in line with the perceptions of followers and also the documentation data that researchers have obtained.